Competitive Ability and Efficiency in Nodule Formation of Strains of Bradyrhizobium japonicum - McDermoti, Timothy R. (1990)
In the American Midwest, superior N(2)-fixing inoculant strains of Bradyrhizobium japonicum consistently fail to produce the majority of nodules on the roots of field-grown soybean. Poor nodulation by inoculant strains is partly due to their inability to stay abreast of the expanding soybean root system in numbers sufficient for them to be competitive with indigenous bradyrhizobia. However, certain strains are noncompetitive even when numerical dominance is not a factor. In this study, we tested the hypothesis that the nodule occupancy achieved by strains is related to their nodule-forming efficiency. The nodulation characteristics and competitiveness of nine strains of B. japonicum were compared at both 20 and 30°C. The root tip marking technique was used, with the nodule-forming efficiency of each strain estimated from the average position of the uppermost nodule and the number of nodules formed above the root tip mark. The competitiveness of the nine strains relative to B. japonicum USDA 110 was determined by using immunofluorescence to identify nodule occupants. The strains differed significantly in competitiveness with USDA 110 and in nodulation characteristics, strains that were poor competitors usually proving to be inferior in both the average position of the uppermost root nodule and the number of nodules formed above the root tip mark. Thus, competitiveness was correlated with both the average position of the uppermost nodule (r = 0.5; P = 0.036) and the number of nodules formed above the root tip mark (r = 0.64; P = 0.005), while the position of the uppermost nodule was also correlated to the percentage of plants nodulated above the root tip mark (r = 0.81; P < 0.001) and the percentage of plants nodulated on the taproot (r = 0.67; P = 0.002).